1998
DOI: 10.1002/(sici)1096-8652(199810)59:2<133::aid-ajh6>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Systemic transforming growth factor‐beta in patients with bone marrow fibrosis—pathophysiological implications

Abstract: Idiopathic myelofibrosis (IMF) and secondary myelofibrosis (MF) are characterized by bone marrow (BM) fibrosis, neoangiogenesis, and increased extracellular matrix (ECM) proteins. These characteristics may be partially attributed to transforming growth factor beta (TGF-␤), a cytokine produced by monocytes. In myelofibrosis, monocytes are increased and activated with concomitant up-regulation of intracytoplasmic TGF-␤. We have therefore determined systemic TGF-␤ in patients with either BM fibrosis: IMF, n = 18;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Detection of high levels of circulating TGF-β1 in HCL patients is an important finding and is in agreement with the recent data of Rameshwar et al, who demonstrated that systemic TGF-β1 is elevated in patients with idiopathic and secondary myelofibrosis (50). TGF-β is usually produced as a large latent complex, and the active form has to be released to produce biological effects (51).…”
Section: Discussionsupporting
confidence: 88%
“…Detection of high levels of circulating TGF-β1 in HCL patients is an important finding and is in agreement with the recent data of Rameshwar et al, who demonstrated that systemic TGF-β1 is elevated in patients with idiopathic and secondary myelofibrosis (50). TGF-β is usually produced as a large latent complex, and the active form has to be released to produce biological effects (51).…”
Section: Discussionsupporting
confidence: 88%
“…85,86 The NF-B pathway has been shown to be activated and implicated in the abnormal release of TGF-␤ in PMF, implying an important role of NF-B activation in the development of bone marrow fibrosis. [87][88][89] As noted previously, TGF-␤ is highly immunosuppressive, impairing the functionality of several immune cells (dendritic cells, NK cells, and cytotoxic T cells) involved in tumor immune surveillance. 61,63 Accordingly, by enhancing TGF-␤ release in the bone marrow, NF-B activation may not only promote fibrosis but also indirectly promote expansion of the malignant clone by suppressing immune cells.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…This is because the mechanisms for myelofibrosis are poorly understood [170][171][172] and the means for quantitating it imprecise due to the patchy nature of the process. 168,[173][174][175] Furthermore, with respect to diagnosis, it has generally been assumed that polycythemia vera and idiopathic myelofibrosis are closely related disorders, 152 although apart from phenotypic similarities, this assumption has never been substantiated scientifically.…”
Section: Myelofibrosismentioning
confidence: 99%